Metaphorical models and the translator’ s approach to scientific texts - Temmerman, Rita (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Indeed, the utility of theory-constitutive metaphor seems to lie largely in the fact that they provide a way to introduce terminology for features of the world whose existence seems probable, but many of whose fundamental properties have yet to be discovered. Theory constitutive metaphors, in other words, represent one strategy for the accommodation of language to as yet undiscovered causal features of the world. (Boyd 1979:364) In this article we investigate the mechanisms behind the urge for better and new understanding. Our hypothesis is that these are generally related to and inspired by metaphorical reasoning. The existing cognitive model of a source domain of understanding is used to structure and categorise a target domain. The metaphorical model is an underlying schema which is not fully expressed propositionally and lexically. The traces and results of metapho¬rical thinking are in metaphorical lexicalisations. We challenge the princi¬ple of traditional Vienna school terminology theory which claims that because unambiguous communication is the ideal in scientific communica¬tion, it is preferable to replace a metaphorical term by its literal equivalent. We show how in the life sciences the gestalt-like metaphorical model which was at the basis of better understanding and new discovery continues to have an important role in didactic as well as in scientific texts which treat the same or related subjects. The discipline of terminology theory could work out guidelines for the description of metaphorical models starting from the metaphorical lexicalisations which are the traces which metaphorical think¬ing leaves in a language. Translators who are aware of the impact of metaphorical reasoning on lexicalisation in scientific language will develop the ability to distinguish between metaphorical models which are language and culture independent and those which are not.